Eksperimen Pembelajaran Matematika Berbasis Realistic Mathematics Education Terhadap Hasil Belajar Ditinjau Dari Kemampuan Komunikasi Matematika Siswa Kelas VII Semester Gasal SMP N 1 Baki Tahun 2015/2016 - Ni'matillah, Rizka (2016)
Rizka Ni'matillah/A410120176. MATH LEARNING EXPERIMENT BASED REALISTIC MATHEMATICS EDUCATION TO LEARNING OUTCOMES VIEWED FROM MATH COMMUNICATION ABILITY 7TH A CLASS FIRST SEMESTER AT SMP N 1 BAKI TERM 2015/2016.Essay.Faculty of Teacher Training and Education.Muhammadiyah University of Surakarta. December, 2015. Learning outcomes is important to know the students' understanding after learning process. Learning approach is needed in order to be a good learning outcomes is Realistic Mathematics Education. In addition, mathematics communication ability also influence the learning outcomes. This research aims to describe and analyze : (1) contribution to mathematics learning based Realistic Mathematics Education on learning outcomes, (2) contribution mathematics communication ability of students on learning outcomes, (3) interaction of mathematics learning based Realistic Mathematics Education and mathematics communication abilitystudents on learning outcomes. The population of this research was students of grade VII in SMP N 1 Baki term 2015/2016. The samples in this research is two classes each comprising 31 students. The first class as a experiments class using learning based on Realistic Mathematics Education and second class as a control class using expository learning. The sampling technique used was simple random sampling. Data collection method used is the test, questionnaire, and documentation. The analysis technique used is a two-way analysis of variance and has previously been tested for normality and homogeneity test. From the results of research on=5% obtainable (1) there are contribution to mathematics learning based Realistic Mathematics Education on learning outcomes with Fobs = 5,573185 > F = 4,01; (2) there are contribution mathematics communication ability of students on learning outcomes withFobs = 15,95437 > F = 3,16; (3) there are interaction of mathematics learning based Realistic Mathematics Education and mathematics communication abilitystudents on learning outcomes with Fobs = 3,445566 > F = 3,16.